Impact of biomass burning emissions and dust on soluble iron deposition to Australian waters, the Southern Ocean and Antarctica - Winton, Victoria Holly Liberty (Curtin University, 2016)
The deposition of atmospheric iron to iron-limited ocean waters around Australia and Antarctica can dramatically stimulate the growth of microscopic marine plants. To date, mineral dust was assumed to be the primary source of iron to the ocean. However, only a small fraction of iron in dust is bioavailable. This study has found that Australian bushfires can indirectly increase the bioavailable iron fraction when smoke and mineral dust mix during long-range atmospheric transport to Antarctica.